Broadly neutralizing antibody-mediated protection against simian-HIV infection among macaques with vaginal sexually transmitted infections. (1st April 2023) - Garber, David A.; Guenthner, Patricia; Zhao, Chunxia; Mitchell, James; Ellis, Shanon; Jia, Hongwei; Manganare, Marcos; Gazumyan, Anna; Seaman, Michael S.; Vishwanathan, Sundaram Ajay; Heneine, Walid; McNicholl, Janet M.
Abstract : Objective: Sexually transmitted infections (STIs) increase mucosal HIV infection risk and have the potential to reduce preexposure prophylaxis efficacy. Clinical trials of a broadly neutralizing antibody (bNAb) provided proof-of-concept that passive immunization against HIV can be efficacious in people. We sought to evaluate preclinically the protective efficacy of passive bNAb immunization against simian-human immunodeficiency virus (SHIV) infection in the context of concurrent vaginal STIs. Design: Using a macaque model of combined ulcerative and nonulcerative vaginal STIs caused by Treponema pallidum, Chlamydia trachomatis, and Trichomonas vaginalis, we determined the protection that passively administered bNAb 10-1074 conferred against repeated vaginal SHIV challenges and compared correlates of protection to contemporaneous and historical controls without STIs. Methods: Plasma viremia was monitored via RT-qPCR assay. Concentrations of 10-1074 were determined longitudinally in plasma samples via TZM-bl pseudovirus neutralization assay. Results: Among macaques with vaginal STIs, a single subcutaneous injection of 10-1074 durably protected against vaginal SHIV acquisition, as compared with untreated controls. Interestingly, the median plasma concentration of 10-1074 at the time of SHIV breakthrough among macaques with STIs was significantly higher (10-fold) than that previously observed among 10-1074-treated macaques in the absence of STIs. Conclusion: Passive immunization with 10-1074 conferred significant protection against repeated vaginal SHIV challenges among macaques harboring vaginal STIs. However, our findings suggest that higher bNAb concentrations may be required for prophylaxis when STIs are present. Our findings potentially impact dose selection for the clinical development of bNAbs and highlight the importance of additional preclinical efficacy testing in STI models.